2022
DOI: 10.3390/ma15010342
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Solid Solution Strengthened Laser Cladded NiCrBSi/WC-12Co Metal Matrix Composite Coatings

Abstract: NiCrBSi, WC-12Co and NiCrBSi with 30, 40 and 50 wt.% WC-12Co coatings were produced on low carbon steel by laser cladding with an Nd:YAG laser with a multi-jet coaxial cladding-nozzle. The microstructure properties after WC-12Co alloying were investigated by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), electron backscatter diffraction (EBSD) and Vickers hardness tests. The resulting microstructures consisted of a γ-Ni and Ni3B matrix, strengthened with Co a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
3
14
0
1
Order By: Relevance
“…The average microhardness of the coatings' surfaces showed only a small difference: C1 -580 HV 1 , C2 -550 HV 1, and C3 -530 HV 1 , despite the relatively disparate deposition parameters used. Nonetheless, a hypothesis test performed in the ®MS Excel software confirmed that they are indeed statistically different, which is in accordance with the literature [16] [25], where hardness reduces for coatings that were deposited faster and that presented higher dilution values. Figures 5(a) and (b) show a comparison between C1, C2, and C3 hardness, scanning speed, and overall dilution.…”
Section: Microhardnesssupporting
confidence: 89%
See 3 more Smart Citations
“…The average microhardness of the coatings' surfaces showed only a small difference: C1 -580 HV 1 , C2 -550 HV 1, and C3 -530 HV 1 , despite the relatively disparate deposition parameters used. Nonetheless, a hypothesis test performed in the ®MS Excel software confirmed that they are indeed statistically different, which is in accordance with the literature [16] [25], where hardness reduces for coatings that were deposited faster and that presented higher dilution values. Figures 5(a) and (b) show a comparison between C1, C2, and C3 hardness, scanning speed, and overall dilution.…”
Section: Microhardnesssupporting
confidence: 89%
“…An increased irregularity in C2 and C3 worn tracks was another indication of their higher wear. Similar considerations are presented in the literature [15,25]. Figure 13(a) shows a worn track profile obtained via the interferometry of a sample tested from C1, while figure 13(b) shows the SEM image of the worn ball used as the counterbody.…”
Section: Worn Counterbodies (Balls) and Debrissupporting
confidence: 53%
See 2 more Smart Citations
“…Yüksek performanslı lazer kaplama malzemeleri üzerine yapılan araştırmalar son yıllarda artmaktadır [5][6][7][8]. Wang ve ark.…”
Section: Introductionunclassified